Perineal body stretch during labor does not predict perineal laceration, postpartum incontinence, or postpartum sexual function: a cohort study. Issue 8 (August 2016) - Meriwether, Kate; Rogers, Rebecca; Dunivan, Gena; Alldredge, Jill; Qualls, Clifford; Migliaccio, Laura; Leeman, Lawrence
Abstract Introduction and hypothesis The perineum stretches naturally during obstetrical labor, but it is unknown whether this stretch has a negative impact on pelvic floor outcomes after a vaginal birth (VB). We aimed to evaluate whether perineal stretch was associated with postpartum pelvic floor dysfunction, and we hypothesized that greater perineal stretch would correlate with worsened outcomes. Methods This was a prospective cohort study of primiparous women who had a VB. Perineal body (PB) length was measured antepartum, during labor, and 6 months postpartum. We determined the maximum PB (PBmax ) measurements during the second stage of labor and PB change (ΔPB) between time points. Women completed functional questionnaires and had a Pelvic Organ Prolapse Quantification (POP-Q) system exam 6 months postpartum. We analyzed the relationship of PB measurements to perineal lacerations and postpartum outcomes, including urinary, anal, and fecal incontinence, sexual activity and function, and POP-Q measurements. Results Four hundred and forty-eight women with VB and a mean age of 24 ± 5.0 years with rare (5 %) third- or fourth-degree lacerations were assessed. During the second stage of labor, 270/448 (60 %) had perineal measurements. Mean antepartum PB length was 3.7 ± 0.8 cm, with a maximum mean PB length (PBmax ) during the second stage of 6.1 ± 1.5 cm, an increase of 65 %. The change in PB length (ΔPB) from antepartum to 6 months postpartum was a net decrease (−0.39 ± 1.02 cm). PB change and PBmax were not associated with perineal lacerations or outcomes postpartum (allp  > 0.05). Conclusions PB stretch during labor is unrelated to perineal laceration, postpartum incontinence, sexual activity, or sexual function.